EVALUATING TRAINING EFFECTIVENESS WITH KIRKPATRICK MODEL AT PT. BUANA CENTRA SWAKARSA - Denardo, Denardo (Yayasan Education and Social Center, 2025)
This study aims to evaluate the effectiveness of the training program at PT. Buana Centra Swakarsa (BCS) using the Kirkpatrick Evaluation Model, which consists of four levels: reaction, learning, behavior, and outcome. The research method used is descriptive quantitative, involving all training participants as respondents. Data were collected through questionnaires, pre- and post-tests, interviews, observations, and secondary data related to costs and company performance. The results of the study indicate that (1) at Level 1, participants were satisfied with the training; (2) at Level 2, there was a significant increase in post-test results compared to the pre-test; (3) at Level 3, the training resulted in positive behavioral changes in the workplace; and (4) at Level 4, the training made a positive and significant contribution to improving work results and company efficiency. However, there are indications that learning strategies need to be adjusted in certain months to ensure a more even distribution of the training's impact. This study concludes that training at PT. BCS is categorized as effective, but improvements in distribution, cost efficiency, and follow-up programs are needed for more optimal results